2009
DOI: 10.1021/jm801178c
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure−Activity Relationships of Trisubstituted Pyrimidines/Pyridines as Novel Calcium-Sensing Receptor Antagonists

Abstract: The trisubstituted pyrimidine 1 was identified through high-throughput screening as a novel calcium-sensing receptor (CaSR) antagonist. Small molecule CaSR antagonists and/or negative allosteric modulators have the potential to act as an anabolic agent for the treatment of osteoporosis. The investigation of structure-activity relationships around 1 resulted in the identification of 18c and 18d, which showed efficacy at promoting PTH release in vivo and exhibited improved potency and solubility over the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…), polyamines (spermine, spermidine), aminoglycoside antibiotics (neomycin, gentamycin), calcimimetics (NPS R-467, NPS R-568), L-amino acids (phenylalanine, tryptophan), trisubstituted pyrimidines and pyridines, and glutathione and amyloid peptides (McLarnon and Riccardi, 2002;Hofer et al, 2004;Wang et al, 2006;Jensen and Bräuner-Osborne, 2007;Yang et al, 2009). Thus, depending on context, CASR can be involved in multiple cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…), polyamines (spermine, spermidine), aminoglycoside antibiotics (neomycin, gentamycin), calcimimetics (NPS R-467, NPS R-568), L-amino acids (phenylalanine, tryptophan), trisubstituted pyrimidines and pyridines, and glutathione and amyloid peptides (McLarnon and Riccardi, 2002;Hofer et al, 2004;Wang et al, 2006;Jensen and Bräuner-Osborne, 2007;Yang et al, 2009). Thus, depending on context, CASR can be involved in multiple cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds will be of great service in future research. Novel allosteric modulators of the CaR are constantly being identified (Gavai et al, 2005;Yang et al, 2009), thus the research on these very important compounds continues and may provide novel treatments for disorders in which CaR sensing is dysregulated. Nevertheless, further targeting methods need to be identified and the specificity of CaR ligands increased to reduce the secondary effects that may occur with the administration of these ligands.…”
Section: Discussionmentioning
confidence: 99%
“…However, NPS2143 has unfavorable pharmacokinetic properties in vivo (see section V.D). Later on, several HTS and lead optimization programs have yielded a number of negative allosteric CaSR modulators from various chemical classes: compounds relatively closely related to NPS2143 (Gavai et al, 2005), but also different molecules, such as Calhex 231 (compound II in Table 13) and derivatives thereof (Petrel et al, 2003;Kessler et al, 2006), trisubstituted pyridines/ pyrimidines (compound V in Table 13) (Arey et al, 2005;Yang et al, 2009), benzyloxy analogs (compound IV in Table 13) (Balan et al, 2009), 2-benzylpyrrolidinesubstituted aryloxypropanols (compound VI in Table 13) , 3H-quinazolin-4-ones (compound VII in Table 13) (Shcherbakova et al, 2005), and 4-arylquinazolin-2-ones (compound VIII in Table 13) (Widler et al, 2010) were identified as novel calcilytics, having essentially similar effects on intracellular calcium mobilization and inositol formation in cellular assay systems, some of them also being active in vivo. More compounds having in vivo activity are discussed below.…”
Section: Allosteric Modulators Of the Calcium Sensing Receptor: "Cmentioning
confidence: 99%